Highly active and stable oxygen vacancies via sulfur modification for efficient catalysis in lithium–sulfur batteries - Zhao, Chenghao; Jiang, Bo; Huang, Yang; Sun, Xun; Wang, Ming; Zhang, Yu; Zhang, Naiqing (Energy & environmental science, 2023)
The introduction of oxygen vacancies (Vo) in lithium–sulfur battery (LSB) catalysts is regarded as an effective approach to improving catalyst performance. However, the high activity of Vo is a double-edged sword, and their instability is usually ignored. Here, we report an “anchor vacancies” method to combine the high activity and high stability of Vo by S modification. The adsorption and catalytic performance of lithium polysulfides (LiPSs) are effectively improved by S modification; meanwhile, S atoms at the surface can anchor nearby vacancies to prevent inward migration due to lowering formation energies, which improves the stability of catalysis. The cells based on this catalyst delivered an initial discharge-specific capacity as high as 1291 mA h g −1 at 0.2C and a low average capacity fading of 0.035% per cycle during 1500 cycles at 1C. This research provides an effective strategy for the improvement of the activity and stability of Vo in LSBs, which carves out a new route for the design of advanced catalysts in LSBs.